Irigaray and politics : a critical introduction - Roberts, Laura (Thinking politics (Edinburgh, Scotland), 2019)
Bringing together Luce Irigaray's early psychoanalytically orientated writings with her more recent and more explicitly political writings, Irigaray and Politics weaves together the ontological, political and ethical dimensions of Irigaray's philosophy of sexuate difference in imaginative ways.